2014
DOI: 10.1007/s11356-014-3658-1
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic removal of paracetamol from aqueous phase: horseradish peroxidase immobilized on nanofibrous membranes

Abstract: Paracetamol is a widely used as an analgesic and an antipyretic that can easily accumulate in aquatic environments. This study aimed to enhance paracetamol removal efficiency from water by combining the biocatalytic activity of horseradish peroxidase (HRP) with the adsorption of nanofibrous membrane. Poly(vinyl alcohol)/poly(acrylic acid)/SiO2 electrospinning nanofibrous membrane was prepared with fiber diameters of 200 to 300 nm. The membrane was made insoluble by the thermal cross-linking process. HRP, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 42 publications
3
24
0
2
Order By: Relevance
“…The maximum value in the normalized enzyme activity was obtained in the pH interval from 4.0 to 7.0. These results are in agreement with the reported enzyme activities for the HRP immobilized in electrospun polymeric nanofibers . This is an important result since several applications involving the use of HRP are carried out in this pH interval, such as biosensors (metal ion sensor, DNA), immunoassays, and wastewater treatment, among others .…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The maximum value in the normalized enzyme activity was obtained in the pH interval from 4.0 to 7.0. These results are in agreement with the reported enzyme activities for the HRP immobilized in electrospun polymeric nanofibers . This is an important result since several applications involving the use of HRP are carried out in this pH interval, such as biosensors (metal ion sensor, DNA), immunoassays, and wastewater treatment, among others .…”
Section: Resultssupporting
confidence: 91%
“…However, the nanofiber diameter distribution showed an increase on its central value from 130 to 872 nm; likely due to the absorption of water molecules inside the PVA nanofiber matrix [Figure (c,d)]. Finally, it is important to point out the quality and extension of this morphology study in comparison with other reported works involving the encapsulation and immobilization of the HRP enzyme using the electrospinning technique . In this section, we were able to see the impact of the different steps of the immobilization process in the morphology of the PVA electrospun nanofibers, as well as the water‐stability of the PVA nanofiber matrix after the submersion in the reaction medium.…”
Section: Resultsmentioning
confidence: 74%
“…19 The functional groups of original and enzyme-immobilized nanobers were determined using a Fourier transform infrared attenuated total reectance (FTIR/ATR, Bruker-Vector 22) spectrometer that was equipped with a germanium crystal. The surface morphology of the CPN EFMs was characterized using scanning electron microscopy (SEM), which was conducted on a eld emission XL-30 SEM at 30 kV.…”
Section: Characterization Of Cpn Efmsmentioning
confidence: 99%
“…8 In another case, the removal efficiency of TBBPA was as high as 99.3% through the use of ozonation. 13 Enzyme immobilization was considered to be applicable for TBBPA removal because of its structural similarity with the pollutants above. By contrast, enzyme immobilization on nanobrous membrane is considered to be a promising technique for the removal of pollutants because of its capability for high efficiency (including both adsorption of nanomaterials and degradation of enzymes), environmentalfriendly, and reusability.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their minimized diffusion limitations, large surface‐to‐volume ratios, and high enzyme loading capability, nanoscale materials are considered as excellent candidates for enzyme immobilization . For example, nanofibrous membranes , chitosan‐halloysite hybrid‐nanotubes , NH 2 ‐modified magnetic Fe 3 O 4 /SiO 2 particles , and graphene oxide are already investigated to show impressive enzyme immobilization ability. However, some of these nanomaterials are restricted for industrial applications by high cost and complicated preparation protocols .…”
Section: Introductionmentioning
confidence: 99%